Mathematics Literacy Ability Seen From Self Efficacy Of Students On Contextual Teaching Learning Model With Direct Corrective Feedback - Utami, Ulfany Fitri; Kartono, Kartono; Wardono, Wardono (Universitas Negeri Semarang, 2021)
This research aims to describe mathematics literacy skill based on students’ self efficacieson Contextual Teacher Learning (CTL) with Direct Corrective Feedback. This mixed method research with sequential explanatory design took population from VIII graders of SMP Negeri 3 Gegesik, Cirebon, in academic year 2018/2019. The sample consisted of VIII A and VIII B. The subjects of VIII A were selected based on three self-efficacy categories: high, moderate, and poor. The techniques of collecting data were mathematics literacy test of the students, self-efficacy questionnaire, and interview. The findings showed that Contextual Teacher Learning (CTL) with Direct Corrective Feedback was effective. The research also described mathematics literacy ability based on the students’ self-efficacies were categorized high, moderate, and poor during CTL with Direct Corrective Feedback. The results were varied where six – high self efficacystudents, three of them were categorized high, two of them moderate, and only one poor level. The moderate self-efficacy students consisted of eleven people with high matehamtics literacy, nine with moderate, and only one with poor level. The poor self-efficacy students did not have high self-efficacy students but only two moderate and one poor self-efficacy students.